2018
DOI: 10.18203/2320-1770.ijrcog20180854
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Pseudotumor Cerebri Syndrome (PTCS) with hormonal contraceptive use

Abstract: Background: Hormonal contraceptives (HC), one of the most prescribed classes of medication in women, have been linked with pseudotumor cerebri syndrome (PTCS). To date, no large epidemiologic study has examined this association.Methods: A case-control study using the IMS LifeLink Pharmetrics Plus database was conducted. Cases had an ICD-9-CM code for benign intracranial hypertension as well as a procedural code for a CT or MRI and a code for lumbar puncture procedure within 15 days of the PTCS code. Controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hormonal contraceptives are not contraindicated in IIH8 and there is no preferred contraceptive method. Previously, case reports have linked oral contraceptives to secondary causes of raised intracranial pressure (pseudotumour cerebri); however, more recent literature has shown that they are not associated with increased incidence of raised intracranial pressure 9–11. We have noted that weight gain can be associated with starting oral contraceptives, and this may be something to explore sensitively with patients.…”
Section: Prepregnancymentioning
confidence: 82%
“…Hormonal contraceptives are not contraindicated in IIH8 and there is no preferred contraceptive method. Previously, case reports have linked oral contraceptives to secondary causes of raised intracranial pressure (pseudotumour cerebri); however, more recent literature has shown that they are not associated with increased incidence of raised intracranial pressure 9–11. We have noted that weight gain can be associated with starting oral contraceptives, and this may be something to explore sensitively with patients.…”
Section: Prepregnancymentioning
confidence: 82%
“…The published studies that have attempted to examine the risk of PTCS with contraceptive medications have all assessed this risk in comparison to non-users of contraceptives. The results from some of these studies were underpowered because of a small number of events [1,2,12], leading to wide CIs. Other studies did not control for all potential confounders including age and BMI [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies using various registries and insurance databases failed to confirm a link with oral contraceptives. [101][102][103][104] Tan et al performed a meta-analysis of articles that reported medicationassociated IH. 105 They found few verifiable cases for contraceptives and were only able to suggest a potentially stronger association with progestin-only preparations compared with combined products.…”
Section: Secondary Intracranial Hypertensionmentioning
confidence: 99%
“…More recent studies have largely refuted the link with oral contraceptives. Multiple studies using various registries and insurance databases failed to confirm a link with oral contraceptives 101–104 . Tan et al performed a meta‐analysis of articles that reported medication‐associated IH 105 .…”
Section: Secondary Intracranial Hypertensionmentioning
confidence: 99%